FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN INTERNET BANKING PADA BANK BCA SURABAYA - Agnes Ayu Wagiri; Dudi Anandya; Indarini Indarini (Perpustakaan Universitas Surabaya, 2018)
This study aimed to examine the determinants of internet banking adoption spesifically in Bank BCA Surabaya using the social cognitive theory. Research findings indicated direct impact of Trust, Compatibility with Lifestyle and Online Customer Service to Intention to Adopt Internet Banking Bank BCA Surabaya.Furthermore, the hypotheses of influence Website’s Social Feature and Ease of Useto Intention to Adopt Internet Banking Bank BCA Surabaya also moderation influence from type of device is not supported.